2015
DOI: 10.1002/ijop.12188
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement, adolescents' self‐determined learning and academic achievement in Urban China

Abstract: Self-determined learning is essential to academic success. The motivational resources development model argues that parents promote academic success in their children indirectly by nurturing self-determined learner. In this study, applying a structural equation modelling and using data collected from 8th graders in Zhuhai, China (n = 1009) in 2012, we aim to answer 2 research questions: (a) What forms of parental involvement are highly correlated with self-determined learning and (b) Can self-determined learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
3
18
0
4
Order By: Relevance
“…Moreover, Barger et al (2019) even found a negative association between parental homework assistance and children's academic adjustment. A similar result has been found in China in an empirical study suggesting that parental homework assistance is not significantly related to adolescents' academic achievement (H. Wang & Cai, 2017).…”
Section: Family Ses Parental Involvement and Adolescents' Academic Achievementsupporting
confidence: 84%
“…Moreover, Barger et al (2019) even found a negative association between parental homework assistance and children's academic adjustment. A similar result has been found in China in an empirical study suggesting that parental homework assistance is not significantly related to adolescents' academic achievement (H. Wang & Cai, 2017).…”
Section: Family Ses Parental Involvement and Adolescents' Academic Achievementsupporting
confidence: 84%
“…However, current public attention on food safety in China is mainly at individual, organizational, and community levels, with an apparent lack of public attention on the characteristics of family-oriented culture and childcentered consumption. Furthermore, within the family, parents' attention to their child is at least partially influenced by modern values such as parental financial support and children's academic success (Wang & Cai, 2017), with little reference to environmental justice or its relationship with their everyday activities. These factors provided the motivation to conduct this study focusing on urban children and their families.…”
Section: Green Education Of Urban Children and Familiesmentioning
confidence: 99%
“…For parents, to guide their adolescents and promote a healthy development in terms of autonomy is specially challenging, but active expressions of parenting could affect adolescent's experience of act willingly based on true interests or internalized values (Soenens et al, 2017). Specifically, parental behaviours that are related with adolescent autonomy include setting rules (Ren et al, 2017), expression of affection (Kocayörük et al, 2015), communication (Wuyts et al, 2018), and involvement (Wang & Cai, 2017).…”
Section: Introductionmentioning
confidence: 99%